A resource unit on Philippine wildlife for secondary schools - Quintana, Violeta Valledor- 1944- (1979)
The purpose of this paper was to prepare a resource unit that can be an introductory course on Philippine wildlife. The study sought to deterine the feasibility of teaching the course by studying and analyzing the student's reactions towards the different activities that were included in the unit. Forty six third year high school students from the Immaculata Academy, Laguna participated in the try-out and evaluation of the activities. The semantic differential technique was used to obtain a comprehensive evaluation of students' perception of the activities. On the whole, the students had very favorable reactions towards the activities - enjoyable, interesting, satisfying, stimulating, informative and relevant.
Vita.
"November, 1979."
Thesis (M.A.T. Biology)--University of the Philippine, Diliman.
Keywords: Wildlife conservation -- Study and teaching (Secondary) -- Philippines -- Los Baños (Laguna) -- Activity programs